Description of the puparium of Hermetia teevani Curran (Diptera, Stratiomyidae) reared from roots of cassava (Manihot esculenta Crantz) - Pujol-Luz, José Roberto; Godoi, Fabio Siqueira Pitaluga De; Oliveira, Charles Martins De; Barros-Cordeiro, Karine Brenda; Mousinho, Lucas Pessanha (Zootaxa, 2023)
The puparium of Hermetia teevani Curran is described, based on 173 specimens reared from cassava roots (Manihot esculenta), in laboratory under controlled conditions until the emergence of the adults. Hermetia teevani is the ninth species with immature stage known for Hermetia, in addition to being recorded for the first time for the Distrito Federal and State of Goiás.